Revisiting the Effect of Emotional Labor: A Multi-Level Investigation in Front-Line Service Teams - Zhao, Xin; Fu, Na; Freeney, Yseult; Flood, Patrick C. (Frontiers in Psychology, 2020)
The main purpose of this study is to consider individuals in teams and to reexamine how emotional labor affects the performance of front-line service team and team members through emotional exhaustion. Multi-source data collection and time-lagged research design was adopted to collect data from matched team members and customers nested in the 82 front-line service teams in a large electronics provider based in China. The findings show that surface acting increases emotional exhaustion which reduces customer loyalty at team level and individual task performance at individual level, supporting a full mediation model. While, deep acting is not associated with emotional exhaustion but is positively linked with team member’s task performance. This study provides evidence for the nested nature of emotional labor and exhaustion in teams.